Checking Gollier and Weitzman's solution of the "Weitzman-Gollier puzzle" - Szabolcs Szekeres (Kiel Institute for the World Economy (IfW), 2017)
In "How should the distant future be discounted when discount rates are uncertain?" (2010) Gollier and Weitzman claimed having solved the Weitzman-Gollier puzzle, concluding from a risk-averse utility maximizing model that Weitzman discounting is qualitatively correct and that when uncertain annual interest rates are highly correlated, long term discount rates are declining functions of time. This paper quantifies a similar model and comes to the opposite conclusion. Weitzman discounting is wrong; there is no puzzle if the correct method is used. Risk-neutral discount rates are growing, rather than declining functions of time under the Weitzman assumptions. Risk-averse discount rates can be declining, but must not be used to discount risky project's cash flows; risk adjusted rates must be used instead. When long term market yields are a growing function of time, it makes no sense to invest in projects of similar risk but lesser yield, irrespective of one's degree of risk-aversion.
Keywords: D61; H43; 330; Weitzman-Gollier puzzle; declining discount rates; discounting